Disability and Masculinities : Corporeality, Pedagogy and the Critique of Otherness - Loeser, Cassandra; Crowley, Vicki; Pini, Barbara (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
The ten empirical chapters in this edited collection contribute to an understanding of masculinities through the lens of disability, and disability through the lens of masculinities. An original and well-researched study, this book takes seriously the multiple points of intersection in the making of disabled masculinities, and will be of particularly interest to scholars of disability, gender and sexualities, cultural studies and pedagogy.- Resumé vydavatel